STUDI KEBERADAAN BAKTERI PATOGEN PADA IKAN KAYU (Katsuwobushi) YANG DIPROSES DENGAN ASAP CAIR - Pulu, Emeliza Kondangduata; Dien, Henny Adeleida; Kaparang, Josefa Tety (Media Teknologi Hasil Perikanan, 2017)
The problems in dried bonito flakes industry nowadays is the high contents of Polycyclic Aromatic Hydrocarbons (PAH) which is can act as carcinogenic agent. The aim of this study was to observe and detect the presence of pathogenic bacteria that may contaminate the dried bonito flakes. The tested parameters include Total Plate Count (TPC) analysis, detection of Coliform, Escherichia coli, Staphylococcus, Salmonella. The results showed that the early drying period had 1,3x104 cfu/g and the final drying had 3x103 cfu/g. There is no evidence of the Â presence of Escherichia coli, Staphylococcus, Salmonella.